UTILIZATION OF THE AIRCRAFT FLIGHT DATA FOR ASSESSMENT OF THE AVIATION WHEEL BRAKES ENERGY STRENGTH - Максимов, Володимир Олексійович; Юрченко, Олена Іванівна (Problems of Friction and Wear, 2019)
The utilization of flight data for assessing of the energy loading of aviation wheel brakes is proposed. The operational ranges of the main characteristics of the aircraft, which affect the load capacity of the wheel brakes, namely, landing speed, landing mass of the different aircraft using the flight data on-board means of objective control and registration (FDR), are studied.